Hexahydrocurcumin protects against cerebral ischemia/reperfusion injury, attenuates inflammation, and improves antioxidant defenses in a rat stroke model - Piyawadee Wicha (2018)
© 2017 Wicha et al. This is an open access article distributed under the terms of the Creative Commons Attribution License, which permits unrestricted use, distribution, and reproduction in any medium, provided the original author and source are credited. The purpose of the present experiment was to investigate whether hexahydrocurcumin (HHC) attenuates brain damage and improves functional outcome via the activation of antioxidative activities, anti-inflammation, and anti-apoptosis following cerebral ischemia/reperfusion (I/R). In this study, rats with cerebral I/R injury were induced by a transient middle cerebral artery occlusion (MCAO) for 2 h, followed by reperfusion. The male Wistar rats were randomly divided into five groups, including the sham-operated, vehicle-treated, 10 mg/kg HHC-treated, 20 mg/kg HHC-treated, and 40 mg/kg HHC-treated I/R groups. The animals were immediately injected with HHC by an intraperitoneal administration at the onset of cerebral reperfusion. After 24 h of reperfusion, the rats were tested for neurological deficits, and the pathology of the brain was studied by 2,3,5-triphenyltetrazolium chloride (TTC) staining, hematoxylin and eosin (H & E) staining, and terminal deoxynucleotidyltrans-ferase UTP nick end labeling (TUNEL) staining. In addition, the brain tissues were prepared for protein extraction for Western blot analysis, a malondialdehyde (MDA) assay, a nitric oxide (NO) assay, a superoxide dismutase (SOD) assay, a glutathione (GSH) assay, and a glutathione peroxidase (GSH-Px) assay. The data revealed that the neurological deficit scores and the infarct volume were significantly reduced in the HHC-treated rats at all doses compared to the vehicle group. Treatment with HHC significantly attenuated oxidative stress and inflammation, with a decreased level of MDA and NO and a decreased expression of NF-κB (p65) and cyclooxygenase-2 (COX-2) in the I/R rats. HHC also evidently increased Nrf2 (nucleus) protein expression, heme oxygenase-1 (HO-1) protein expression, the antioxidative enzymes, and the superoxide dismutase (SOD) activity. Moreover, the HHC treatment also significantly decreased apoptosis, with a decrease in Bax and cleaved cas-pase-3 and an increase in Bcl-X L , which was in accordance with a decrease in the apoptotic neuronal cells. Therefore, the HHC treatment protects the brain from cerebral I/R injury by diminishing oxidative stress, inflammation, and apoptosis. The antioxidant properties of HHC may play an important role in improving functional outcomes and may offer significant neuroprotection against I/R damage.